175 A Fas-4–1BB immunomodulatory fusion protein converts a pro-death to a pro-survival signal, enhancing T cell function and efficacy of adoptive cell therapy in murine models of AML and pancreatic cancer. (10th December 2020) - Oda, Shannon; Anderson, Kristin; Greenberg, Philip; Garcia, Nicolas; Ravikumar, Pranali; Bonson, Patrick; Jenkins, Cody; Zhuang, Summer; Daman, Andrew; ,
Abstract : Background: Adoptive cell therapy (ACT) with genetically-modified T cells has shown impressive results against some hematologic cancers, but limited efficacy against tumors with restrictive tumor microenvironments (TMEs). FasL is a particular obstacle for ACT; 1 it is expressed in many tumors and TMEs, 1 including AML, 2 ovarian 3 and pancreatic cancers, 4 and upregulated on activated T cells, where it can mediate activation-induced cell death (AICD). 5 Methods: We engineered T cells to boost function with novel immunomodulatory fusion proteins (IFPs) that combine an inhibitory ectodomain with a costimulatory endodomain. Like current checkpoint-blocking therapies, IFPs can abrogate an inhibitory signal, but also provide an often absent costimulatory signal. Additionally, IFP-driven signals are delivered only to the T cells concurrently engineered to be tumor-specific, thereby avoiding systemic T cell activation. For FasL-expressing TMEs, we developed an IFP that replaces the Fas intracellular tail with costimulatory 4-1BB. We tested the the Fas-4-1BB IFP in primary human T cells and in immunocompetent murine models of leukemia and pancreatic cancer. Results: Fas-4-1BB IFP expression enhanced primary human T cell function and enhanced lysis of Panc1 pancreatic tumor cells in vitro. Fas-4-1BB IFP-engineered murine T cells exhibited increased pro-survival signaling, proliferation, antitumor function and altered metabolism in vitro. Notably, the Fas ectodomain is trimeric 5 and the 4-1BB intracellular domain requires trimerization to signal. 6 In contrast, the CD28 domain is dimeric and did not enhance function when paired with 4-1BB.In vivo, Fas-4-1BB increased T cell persistence and function, and Fas-4-1BB T cell ACT significantly improved survival in a murine AML model. When delivered with a mesothelin-specific TCR, Fas-4-1BB T cells prolonged survival in the autochthonous KPC pancreatic cancer model, increasing median survival to 65 from 37 days (with TCR-only, **P=0.0042). Single-cell RNA sequencing revealed differences in the endogenous tumor-infiltrating immune cells, included changes in cell frequency and programming. Conclusions: We developed an engineering approach to enhance the in vivo persistence and antitumor efficacy of transferred T cells. Our targeted, two-hit strategy uses a single fusion protein to overcome a death signal prevalent in the TME of many cancers and on activated T cells, and to provide a pro-survival costimulatory signal to T cells. Our results suggest that this fusion protein can increase T cell function when combined with murine or human TCRs, and can significantly improve therapeutic efficacy in liquid and solid tumors, supporting clinical translation. References: Yamamoto, T.N., et al., T cells genetically engineered to overcome death signaling enhance adoptive cancer immunotherapy. J Clin Invest 2019. Contini P, et al., In vivo apoptosis of CD8(+) lymphocytes in acute myeloid leukemia patients: involvement of soluble HLA-I and Fas ligand. Leukemia 2007;21(2):p. 253–60. Motz GT, et al., Tumor endothelium FasL establishes a selective immune barrier promoting tolerance in tumors. Nat Med 2014;20(6):p. 607–15. Kornmann M, et al., Fas and Fas-ligand expression in human pancreatic cancer. Ann Surg 2000. 231(3): p. 368–79. Villa-Morales M and J Fernandez-Piqueras, Targeting the Fas/FasL signaling pathway in cancer therapy. Expert Opin Ther Targets 2012;16(1):p. 85–101. Wyzgol, A., et al., Trimer stabilization, oligomerization, and antibody-mediated cell surface immobilization improve the activity of soluble trimers of CD27L, CD40L, 41BBL, and glucocorticoid-induced TNF receptor ligand. J Immunol 2009;183(3):p. 1851–61.